Pore‐scale multiphase flow experiments in bead packs of variable wettability. Issue 1 (17th June 2013) - Celauro, J. G.; Torrealba, V. A.; Karpyn, Z. T.; Klise, K. A.; McKenna, S. A.
Abstract The aim of this experimental study is to investigate the impact of wetting characteristics on multiphase flow, sweep efficiency, and residual fluid distribution in unconsolidated porous media. A sequence of oil and water injections was performed on bead packs with uniform porosity and permeability, but different wettability characteristics. Uniform and mixed‐wet bead packs with varying degree of wettability were fabricated to analyze how the residual saturation profiles and the distribution of fluid phases at the pore scale respond to changes in wettability. X‐ray microtomography was used to visualize and analyze the fluid distribution in each bead pack at the end of oil and brine injection. It was found that sweep efficiency was high for the uniform, strongly wetting glass bead pack. For the intermediate‐wet plastic bead pack, we observed evidence of viscous fingering resulting in degenerating sweep efficiency after water injection. In media with mixed wetting surfaces, the spatial distribution of wettability influenced the topology of the saturation profiles and resulted in larger quantities of disconnected fluid blobs. Results also showed that the average blob size was independent of the average residual saturation. In addition, the difference in saturation conditions preceding each injection affected sweep efficiency. The residual saturation after the 1st displacement was higher than the residual saturation after the 2nd displacement.